Simulasi Pelajaran Terpadu Terhubung - Yustika Ratna Sari; Neng Ulfa Masyripah; Ayi Nurajijah (Edu Happiness : Jurnal Ilmiah Perkembangan Anak Usia Dini, 2022)
Often we as educators find it difficult to approach our students with various types of attitudes, some of them tend to be open, some are very closed, so we have to try anything so that we can easily interact well and the delivery of material will be very comfortable. The purpose of this connected integrated learning simulation is so that children can express their ideas, ideas and can display what they can / have also so that children can easily interact with the lessons that we convey so that they can also increase the student's participation. The method I use is an approach to students in learning that intentionally relates several aspects both intra-subject and inter-subject And the benefit is that with the guidance, students will gain knowledge and skills as a whole so that learning becomes meaningful for students and when compared to conventional concepts, integrated learning seems to emphasize the involvement of students in learning, so that students are actively involved in the learning process. for decision making. From the results of the study, it shows that in the social emotional field, the child shows a sense of empathy or concern, can help each other and work together, the most important thing is that the child starts to get along and knows how to interact with his friends, now the child has started to dare to ask and ask questions during the question and answer session when learning takes place.